2020
DOI: 10.3390/ijms22010226
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Proteomic Biomarker Candidates in Mucopolysaccharidosis Type IVA

Abstract: Mucopolysaccharidosis type IVA (MPS IVA) is a lysosomal storage disease caused by mutations in the N-acetylgalactosamine-6-sulfatase (GALNS) gene. Skeletal dysplasia and the related clinical features of MPS IVA are caused by disruption of the cartilage and its extracellular matrix, leading to a growth imbalance. Enzyme replacement therapy (ERT) with recombinant human GALNS has yielded positive results in activity of daily living and endurance tests. However, no data have demonstrated improvements in bone lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 81 publications
3
18
0
Order By: Relevance
“…After obtaining written informed consent, blood samples from MPS IVA patients were acquired for proteomic analysis of plasma from three Spanish centers of reference for MPS IVA: eight from untreated MPS IVA patients; and five from MPS IVA patients who had been undergoing ERT for a mean duration of 7 years, and from whom samples were taken 24 h before (ERT-a group) and 24 h after (ERT-b group) one of their weekly ERT infusions. All patients presented the classical phenotype as is shown in the previous study [ 32 ]. Another 6 blood samples were acquired from 6 healthy donors ( Figure 15 ).…”
Section: Methodssupporting
confidence: 59%
See 3 more Smart Citations
“…After obtaining written informed consent, blood samples from MPS IVA patients were acquired for proteomic analysis of plasma from three Spanish centers of reference for MPS IVA: eight from untreated MPS IVA patients; and five from MPS IVA patients who had been undergoing ERT for a mean duration of 7 years, and from whom samples were taken 24 h before (ERT-a group) and 24 h after (ERT-b group) one of their weekly ERT infusions. All patients presented the classical phenotype as is shown in the previous study [ 32 ]. Another 6 blood samples were acquired from 6 healthy donors ( Figure 15 ).…”
Section: Methodssupporting
confidence: 59%
“…From these ERT-treated patients, samples were acquired 24 h before (ERT-a) and 24 h after (ERT-b) one of their weekly infusions ( Figure 1 ). The demographic features of the participating MPS IVA patients have been previously described [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we demonstrated that using a combination of shotgun proteomics with SWATH-MS [ 74 , 75 , 76 ] can provide useful information about mucopolysaccharidosis type IVA (MPS IVA). Moreover, this technique can be scaled to accommodate thousands of samples without compromising measurement precision.…”
Section: Proteomics For the Study Of Imdmentioning
confidence: 99%